Psoriatic Arthritis 2018
DOI: 10.1136/annrheumdis-2018-eular.5663
|View full text |Cite
|
Sign up to set email alerts
|

AB0922 Metabolic syndrome is associated with active disease in psoriatic arthritis and may contribute to development of syndesmophytes

Abstract: BackgroundAn increased prevalence of metabolic syndrome (MetS) has been reported in psoriatic arthritis (PsA) suggesting an association between the inflammation and MetS.ObjectivesThe aim of this study is to investigate its relationship with disease activity in patients with PsA. We also evaluated whether an association exists between MetS and axial involvement in PsA.MethodsThis study included patients with PsA followed in the Rheumatology outpatient clinic at Dokuz Eylul University. Age-matched patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…1). Ultimately, 66 of the 84 studies were excluded from inclusion in the systematic literature review (Table 1) [12,, and 18 articles were included [9,14,[83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98], one of which had been identified from the hand search (see Tables 2 and 3 for more detail).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…1). Ultimately, 66 of the 84 studies were excluded from inclusion in the systematic literature review (Table 1) [12,, and 18 articles were included [9,14,[83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98], one of which had been identified from the hand search (see Tables 2 and 3 for more detail).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies included in the systematic literature review were cross-sectional [9,84,85,[87][88][89][90][92][93][94][95][96][97], although prospective observational studies were also found [14,83,86,91,98], and most were of moderate quality (predominantly Oxford CEBM levels of evidence 2b or 4). The total number of PsA patients included in each study ranged from 3571 [91] to 40 [97].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations